Effect of enhanced recovery after surgery on older patients undergoing transvaginal pelvic floor reconstruction surgery: a randomised controlled trial - Xuezhu Huang; Sisi Deng; Xiaofeng Lei; Shentao Lu; Ling Dai; Chunyan She (BMC Medicine)
Abstract Background Prospective trial evidence is lacking regarding the application of enhanced recovery after surgery (ERAS) in transvaginal pelvic floor reconstruction surgery among older patients. Our study aimed to investigate whether implementing the ERAS protocol could enhance post-operative recovery in this patient population. Methods Older patients undergoing elective transvaginal pelvic floor reconstruction surgery were randomly assigned to either the ERAS group or the conventional group. The primary outcome was post-operative length of stay (LOS). The secondary outcomes encompassed other post-operative recovery metrics, post-operative pain within 30 days, the occurrence of complications, the peri-operative blood test and cognitive function. Results A cohort of 100 patients was enrolled. Implementation of the ERAS protocol significantly reduced the duration of post-operative LOS (74.00 (69.00, 96.00) vs. 65.00 (59.00, 78.25) h, P < 0.01). Additionally, the ERAS protocol significantly reduced the duration of the first oral intake post-operatively (5.00 (2.50, 7.00) vs. 3.00 (2.00, 4.00) h, P = 0.01), and reduced rest and movement-related pain within 48 h post-operatively, effects that persisted through the 7-day follow-up period. It also shortened the duration of post-operative laryngeal mask airway support and promoted opioid-sparing. Moreover, the incidence and severity of post-operative nausea and vomiting (PONV) were significantly lower in the ERAS group compared to the conventional group at 12 h post-operatively. Conclusions Implementation of the ERAS protocol can expedite post-operative recovery in older patients undergoing transvaginal pelvic floor reconstruction surgery, achieve opioid-sparing, alleviate pain post-operatively, and decrease the incidence of complications. Trial registration This study was retrospectively registered with the Chinese Clinical Trial Registry (registration number: ChiCTR2400084608). The date of first registration was 21/05/2024.